Peningkatan Nilai Tawar Pasar Tradisional Melalui Healthy Market Berbasis Wakaf - Rizky Fauzi, Muchamad; Sirri, Ahmad; Chandra Ramadhan, Fariz (Jurnal Perbankan Syariah, 2021)
Abstract: The amount of traditional markets in Indonesia is enormous. However, the development of traditional markets is not proportional to the number. The emergence of modern shopping centers has made traditional markets gradually decline. The purpose of this study is to determine the concept of healthy markets based on cash waqf as means of increasing the competitiveness of traditional markets. This study used a descriptive qualitative method by conducting interviews with several sources. This research shows that there are 3 (three) stages in the cash waqf fund-based traditional market competitiveness in the cash waqf-based Healthy Market program, there are: 1) repairment and development of infrastructure, 2) creating healthy and environmentally friendly markets and 3) empowerment of SME. Abstrak: Jumlah Pasar Traditional di Indonesi sangatlah banyak. Akan tetapi perkembangan pasar tradisional tidak sebanding dengan jumlahnya. Munculnya pusat-pusat perbelanjaan modern menjadikan pasar tradisional sedikit demi sedikit mengalami kemunduran. Tujuan dari penelitian ini adalah untuk mengetahui konsep Healthy Market berbasis wakaf tunai sebagai sarana peningkatan daya saing pasar tradisional. Paper ini menggunakan metode kualitatif deskriptif dengan melakukan wawancara pada beberapa narasumber. Penelitian ini memberikan hasil bahwa peningkatan daya saing pasar tradisional berbasis dana wakaf tunai terdapat 3 (tiga) tahap dalam program Healthy Market berbasis wakaf tunai antara lain: 1) perbaikan dan pembangunan infrastruktur, 2) menciptakan pasar sehat dan ramah lingkungan dan 3) pemberdayaan UMKM.